ChemInform Abstract: Recent Advances in the Electrolytes for Interfacial Stability of High‐Voltage Cathodes in Lithium‐Ion Batteries. Issue 13 (March 2015) - Choi, Nam‐Soon; Han, Jung‐Gu; Ha, Se‐Young; Park, Inbok; Back, Chang‐Keun
Abstract Review: 120 refs.